The Effect of Increased Physical Activity on Sexual Functioning in Overweight and Obese Males - Botlani Esfahani, Saeideh (Curtin University, 2023)
This thesis reports the results of a 12 week experimental clinical trial with sedentary overweight and obese males from the Perth community (Australia), intended to determine the effectiveness of increased physical activity to improve sexual functioning by way of effects on depression, anxiety, stress, body image, self-esteem and general health (psychological mediators) and lipids, insulin, glucose, and blood pressure (physiological mediators).